2020
DOI: 10.1136/sextrans-2019-054309
|View full text |Cite
|
Sign up to set email alerts
|

How to increase chlamydia testing in primary care: a qualitative exploration with young people and application of a meta-theoretical model

Abstract: ObjectiveThe objective of this study was to explore young people’s perspectives barriers to chlamydia testing in general practice and potential intervention functions and implementation strategies to overcome identified barriers, using a meta-theoretical framework (the Behaviour Change Wheel (BCW)).MethodsTwenty-eight semistructured individual interviews were conducted with 16–24 year olds from across the UK. Purposive and convenience sampling methods were used (eg, youth organisations, charities, online platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…This is similar to findings from a study on young people’s views on testing in general practice who preferred the guidance of a healthcare professional on how to self-sample for chlamydia. 26 Furthermore, where young people in the present study had concerns about whether STIs could be treated or not, the option of returning to the same pharmacist to obtain chlamydia treatment was both convenient and reassuring for them. Therefore, a potential pharmacy test-and-treat service may encourage further uptake compared with testing alone.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This is similar to findings from a study on young people’s views on testing in general practice who preferred the guidance of a healthcare professional on how to self-sample for chlamydia. 26 Furthermore, where young people in the present study had concerns about whether STIs could be treated or not, the option of returning to the same pharmacist to obtain chlamydia treatment was both convenient and reassuring for them. Therefore, a potential pharmacy test-and-treat service may encourage further uptake compared with testing alone.…”
Section: Discussionmentioning
confidence: 83%
“…A key finding of this study was the role played by young people’s concerns about stigma in obstructing uptake of testing for chlamydia, which is consistent with the literature. 22–25 Furthermore, this paper adds to studies where young people had privacy concerns about the pharmacy environment 6 12 14 18 and about other comparable settings for testing, including general practice 26 and non-medical venues, 27 by suggesting that the concern is linked to perceived stigma. While young people in the present study who used a pharmacy sexual health service and chlamydia testing were happy with the service, promotional activities should also focus on young people who felt uncomfortable in accessing the pharmacy and young men, due to privacy and stigma concerns.…”
Section: Discussionmentioning
confidence: 91%
“…When implementing new programs, there is a need for patient buy-in and acceptance of new STI testing and treatment services. For self-sampling programs, McDonagh et al 19 interviewed 28 people aged 16 to 24 years in the United Kingdom. Participants noted several barriers to testing including physical capability, psychological capabilities, reflective motivation, automatic motivation, physical opportunity, and social opportunity.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in this review showed that self-sampling is generally acceptable to patients. 19 , 22 , 23 However, patient characteristics such as previous interactions with the health care system were shown to affect willingness to wait for results during a visit. Therefore, it is important continue to evaluate the acceptability of these programs among patients and providers to understand how their willingness to promote and use new services impacts adoption and utilization new screening strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, our analyses move the field forwards from simple descriptions of barriers and facilitators to notification, and instead provide detailed and concrete ways of intervening. These approaches have been used to improve various health outcomes such as increasing chlamydia testing in primary care (McDonagh et al, 2020) and enhancing nurses' use of electronic medication management systems (Debono et al, 2017).…”
Section: What Have We Uniquely Done Here?mentioning
confidence: 99%